Health promotion in elderly patients with hyponatremia related to polypharmacy: The nurse’s role - Santos , Cássia Rosa da Silva; Morais , Estefany Bruna Alves da Silva; Biano , Patrick de Sousa Siqueira; Oliveira , Katiulcy Carvalho (Seven Editora, 2023)
Hyponatremia is a condition with a low concentration of sodium in the body that presents itself occasionally in long-lived patients, with greater aggravations in a scenario of polymedications. Objective: To analyze articles that address the theme: The importance of nurses’ performance in health promotion in elderly people with hyponatremia. Method: This paper is a systematic literature review of integrative evaluation. The results find the necessary correlation between professional development, characteristics of the elderly person with hyponatremia and its implications regarding polymedication. Nurses are the main agents in health promotion, they know all the particularities of their patients, plan, implement and participate in the entire process. This work was developed with the purpose of sensitizing and providing learning to professionals, so that they are more engaged and participate in a more assertive way in the promotion of the health of the population in which they work. DOI:https://doi.org/10.56238/innovhealthknow-056